Comparative Metabolomic and Transcriptomic Studies Reveal Key Metabolism Pathways Contributing to Freezing Tolerance Under Cold Stress in Kiwifruit - Sun, Shihang; Fang, Jinbao; Lin, Miaomiao; Hu, Chungen; Qi, Xiujuan; Chen, Jinyong; Zhong, Yunpeng; Muhammad, Abid; Li, Zhi; Li, Yukuo (Frontiers in Plant Science, 2021)
Cold stress poses a serious treat to cultivated kiwifruit since this plant generally has a weak ability to tolerate freezing tolerance temperatures. Surprisingly, however, the underlying mechanism of kiwifruit’s freezing tolerance remains largely unexplored and unknown, especially regarding the key pathways involved in conferring this key tolerance trait. Here, we studied the metabolome and transcriptome profiles of the freezing-tolerant genotype KL (Actinidia arguta) and freezing-sensitive genotype RB (A. arguta), to identify the main pathways and important metabolites related to their freezing tolerance. A total of 565 metabolites were detected by a wide-targeting metabolomics method. Under (-25 °C) cold stress, KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway annotations showed that the flavonoid metabolic pathways were specifically upregulated in KL, which increased its ability to scavenge for reactive oxygen species (ROS). The transcriptome changes identified in KL were accompanied by the specific upregulation of a codeinone reductase gene, a chalcone isomerase gene, and an anthocyanin 5-aromatic acyltransferase gene. Nucleotides metabolism and phenolic acids metabolism pathways were specifically upregulated in RB, which indicated that RB had a higher energy metabolism and weaker dormancy ability. Since the LPCs (LysoPC), LPEs (LysoPE) and free fatty acids were accumulated simultaneously in both genotypes, these could serve as biomarkers of cold-induced frost damages. These key metabolism components evidently participated in the regulation of freezing tolerance of both kiwifruit genotypes. In conclusion, the results of this study demonstrated the inherent differences in the composition and activity of metabolites between KL and RB under cold stress conditions.